Bond Ratings and Company Value: Insights from Indonesia’s Real Estate Sector - Efni, Yulia; Marzolina, M.; Restuti, Sri; Atami, Aulia Pinto (Journal of Ecohumanism, 2024)
This study investigates the impact of bond ratings on company value, mediated by investment decisions, funding decisions, and corporate governance disclosure, focusing on property and real estate companies listed on the Indonesia Stock Exchange (IDX). Using data from 45 companies over a five-year period (2016-2020), this research employs WarpPLS, a variance-based structural equation modeling (SEM) technique, to analyze both direct and indirect effects between the variables. The findings reveal that while investment decisions have a significant positive effect on company value, funding decisions, bond ratings, and corporate governance disclosure do not show direct impacts. However, bond ratings significantly influence company value indirectly through investment decisions. These results highlight the critical role of strategic investment management in enhancing firm value within Indonesia’s property and real estate sector, suggesting that companies should focus on improving bond ratings to facilitate more favorable investment opportunities. The practical implications of these findings suggest that firms should prioritize capital allocation decisions that align with long-term growth objectives to optimize market valuation.